PERHITUNGAN BEBAN PENDINGIN PADA GEDUNG TERMINAL 2 BANDAR UDARA INTERNASIONAL JUANDA - Septian Dwi Nugroho; Suhariyanto; Hadi Kusnanto; Solikin (Universitas Muhammadiyah Surabaya, 2023)
Juanda International Airport is the number 2 busiest airport with a total of 4,316,508 service users in 2022 (BPS, 2022). The increase in the number of service users along with the easing of air travel requirements can cause frequent complaints from service users regarding the air temperature that is felt to be uncomfortable in the terminal area. Given the importance of the existence of a passenger departure terminal, the availability of facilities according to service standards is also a point that needs to be considered. The intended service standard includes departure and arrival facilities at a terminal which includes services for prospective passengers and passengers at the airport terminal. One of the facilities considered in the departure and arrival process is air conditioning (PM 178 2015) and ASHARAE. The author here performs calculations and analysis of cooling loads in the Terminal 2 Building on floors 1 and 2 covering 26 areas. After calculating, it was found that several areas of cooling load exceeded the capacity of the previous existing FCU with the following data: Arrival Immigration according to CLTD calculations of 1,183,444 BTU/h while FCU capacity is 684,019 BTU/h, POTS according to CLTD calculations is 346,197 BTU/h while FCU capacity is 150,000 BTU/h, SCP according to CLTD calculations is 343,338 BTU/h while FCU capacity is 355,650 BTU/h, RT Gate 1- 6 according to CLTD calculations is 1,687,433 BTU/h while FCU capacity is 1,439,550 BTU/h. Keywords: CLTD, ASHRAE, BTU/h.